2021
DOI: 10.1109/access.2021.3071297
|View full text |Cite
|
Sign up to set email alerts
|

Automated Breast Mass Classification System Using Deep Learning and Ensemble Learning in Digital Mammogram

Abstract: In recent years, deep learning techniques are employed in the mammography processing field to reduce radiologists' costs. Existing breast mass classification systems are implemented using deep learning technologies such as a Convolutional Neural Network (CNN). CNN based systems have attained higher performance than the machine learning-based systems in the classification task of mammography images, but a few issues still exist. Some of these issues are; ignorance of semantic features, analysis limitation to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(23 citation statements)
references
References 53 publications
0
23
0
Order By: Relevance
“…In the stacking approach, the outputs from different classification models are to be aggregated into a new dataset [40]. Readers interested for more information are referred to [41]- [46].…”
Section: Related Workmentioning
confidence: 99%
“…In the stacking approach, the outputs from different classification models are to be aggregated into a new dataset [40]. Readers interested for more information are referred to [41]- [46].…”
Section: Related Workmentioning
confidence: 99%
“…Another study reported the use of combined k-mean clustering, long short-term memory (LSTM) network of recurrent neural network (RNN), CNN, random forest, and boosting methods to classify breast masses into three categories: normal, benign, and malignant by Malebary and Hashmi in 2021 [36]. In addition, they compared their invented models with other models utilizing DDSM and MIAS datasets.…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, the AUC was 0.9970−1.0000, sensitivity was 0.9799−1.0000, precision was 0.9758−0.9992, F1-score was 0.9779−0.9996, specificity was 0.9797−0.9993, and kappa was 0.9595−0.9992. Compared to [36], in terms of sensitivity, specificity, F1-score, accuracy, and AUC, as shown in Tab. 1, our results showed 2%−6% enhancements.…”
Section: : Accuracy and Loss Average Of 5-fold Cross-validation For T...mentioning
confidence: 99%
“…Lotter et al’s annotation-efficient deep learning strategy for mammograms and digital breast tomosynthesis image-based breast cancer diagnosis has been proposed by Lotter et al (2021) . Malebary and Hashmi. (2021) suggested an ensemble-based technique for classifying breast masses.…”
Section: Introductionmentioning
confidence: 99%